2012
DOI: 10.1038/jcbfm.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Induces Long-Lasting Deficits in the Temporal Fidelity of Sensory Processing in the Somatosensory Cortex

Abstract: Recovery from stroke is rarely complete as humans and experimental animals typically show lingering deficits in sensory function. One explanation for limited recovery could be that rewired cortical networks do not process sensory stimuli with the same temporal precision as they normally would. To examine how well peri-infarct and more distant cortical networks process successive vibrotactile stimulations of the affected forepaw (a measure of temporal fidelity), we imaged cortical depolarizations with milliseco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…These regions could include those that receive common thalamic input or send axonal projections to neighboring targets. For example, motor cortex, primary somatosensory cortex, and secondary somatosensory cortex all receive thalamic input (Hunnicutt et al, 2014;Oh et al, 2014), and function in secondary areas can be preserved after stroke to primary somatosensory areas (Sweetnam and Brown, 2013). In the rodent motor cortex, for example, the strongest intracortical connections are with the rest of the sensory-motor cortex in the same hemisphere, but strong interhemispheric connections also exist with homotopic areas (Bauer et al, 2014).…”
Section: Major Themes Of Circuit Disruption and Recovery: Diaschisis mentioning
confidence: 99%
“…These regions could include those that receive common thalamic input or send axonal projections to neighboring targets. For example, motor cortex, primary somatosensory cortex, and secondary somatosensory cortex all receive thalamic input (Hunnicutt et al, 2014;Oh et al, 2014), and function in secondary areas can be preserved after stroke to primary somatosensory areas (Sweetnam and Brown, 2013). In the rodent motor cortex, for example, the strongest intracortical connections are with the rest of the sensory-motor cortex in the same hemisphere, but strong interhemispheric connections also exist with homotopic areas (Bauer et al, 2014).…”
Section: Major Themes Of Circuit Disruption and Recovery: Diaschisis mentioning
confidence: 99%
“…These changes were also observed in iPMv and cPMv, and more pronounced with movements of the paretic hand. Similarly, stroke in the somatosensory cortex induces chronic impairments in the temporal fidelity of responses to peripheral stimulation ( Sweetnam and Brown, 2013 ), which could be because of a dysfunction of the corticothalamic feedback circuit involved in the inhibition of thalamocortical neurons ( Paz et al, 2010 ). In the visual system, corticothalamic feedback from the visual cortex to the lateral geniculate nucleus is involved in spike-timing precision of thalamic neurons' responses to incoming visual signals ( Hasse and Briggs, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have used noninvasive imaging methods based on indirect metabolic measures ( Ward, 2015 ; Crofts et al, 2020 ). To date, direct in vivo recording of the impact of brain injury on neuronal activity has revealed that cortical inactivation or lesion profoundly alters processing of sensory information in the two hemispheres ( Meyer et al, 1985 ; Takatsuru et al, 2009 ; Sweetnam and Brown, 2013 ; Kokinovic and Medini, 2018 ), even within minutes after injury ( Sakatani et al, 1990 ; Ding et al, 2011 ; Mohajerani et al, 2011 ). Such rapid neuronal changes can be viewed as consequences of the lesion on the network's homeostasis ( von Monakow, 1914 ; Carrera and Tononi, 2014 ), with a questionable active involvement in motor function at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…Both, VSDs and VSFPs respond to changes in transmembrane voltage in the millisecond time scale, by changing their fluorescence properties [but resolving single action potentials is still limited ( Akemann et al, 2009 )]. Several studies have recently applied VSDs on experimental models of stroke to image functional reorganization of forelimb cortex areas ( Brown et al, 2009 ; Figure 4A ) and long-lasting impairments on the processing of sensory stimuli by the forelimb somatosensory cortex ( Sweetnam and Brown, 2013 ). Weerakkody et al (2013) applied VSD imaging to study the cortical activity after implantation of NSCs into the ventricle of naïve mice.…”
Section: Fluorescence Imagingmentioning
confidence: 99%